Influence of intake air temperature control on characteristics of a Homogeneous Charge Compression Ignition engine for hydrogen-enriched kerosene-dimethyl ether usage. (21st August 2020) - Yontar, Ahmet Alper; Zhou, Mengni; Ahmad, Saif
Abstract: In this study, the high-speed of 2000 rpm and low-speed of 1000 rpm behaviors on the HCCI test engine at full load were examined experimentally by controlling the intake air temperature. The tests were carried out at 0.90 equivalence ratio for hydrogen-enriched kerosene-dimethyl ether mixture. In order to expand the usage of HCCI engines in daily life, their problems encountered at high loads and high speeds need to be solved. The main reason of these problems is the control of the start of combustion since there is no external combustion system in HCCI engines. The experimental results show that the intake air temperature directly affects engine performance and emissions. The intake air temperature control was led to shorter flame development time and better combustion stability. The in-cylinder pressure at 1000 rpm for 373 K is overall 6.82% and 4.07% higher than the 273 K and 298 K. The average heat release rate curve trends at 1000 rpm are overall 45.68% higher than 2000 rpm. The brake specific fuel consumption for 2000 rpm is about 5.29% higher than 1000 rpm. The differences between the two NOx trends are 35.4% maximum and 11.03% minimum for 1000 rpm and 2000 rpm. At high engine speed, the HC formation drops linearly from 488 ppm to 339 ppm with increasing air temperature. Also, the soot formation decreased with a slope of 1.58 times higher than 1000 rpm. Overall, the increase in intake air temperature at the tests positively affected in-cylinder pressure, CO, HC and soot. Highlights: The intake air temperature control effects for the HCCI engine were examined. Hydrogen-enriched kerosene-dimethyl ether was used at high and low engine speeds. The increase in intake air temperature positively affected in-cylinder pressure. The HC formation had dropped linearly with increasing intake air temperature. The intake air temperature rises had a negative effect on BTE, BSFC and NOx .